Analysis of reliability factors of MEMS disk resonator under the strong inertial impact - 董林玺 俞权 包金艳 陶家平 (Journal of semiconductors, 2014)
Increasing the bias voltage is a method of reducing the motional resistance of the capacitive disk res- onator to match the impedance of the RF circuit. But there are few reports on the study of reliable working range of bias voltage under the shock and vibration environment. Therefore, the reliability of disk resonator under the step and pulse acceleration impact respectively is systematically analyzed in this paper. By the expression of the biggest inertial acceleration the disk can bear under the reliable condition, the maximal reliable range curves of the disk resonator under the dynamic impact environment are obtained. According to the actual sizes of disk in the literature, it can be seen that when a step shock of 13000g is supplied, the reliability range is reduced to 75% compared with the original state. For the pulse shock, the reliability range is related to the pulse amplitude and time width. Research of this paper can provide the basis for the selection of bias voltage of disk resonator under the inertial shock.